Wanting to be 'with woman', not with machine: Midwives' experiences of caring for women being continuously monitored in labour. Issue 4 (July 2022) - Fox, Deborah; Coddington, Rebecca; Scarf, Vanessa
Abstract: Problem: Some continuous electronic fetal monitoring (CEFM) devices restrict women's bodily autonomy by limiting their mobility in labour and birth. Background: Little is known about how midwives perceive the impact of CEFM technologies on their practice. Aim: This paper explores the way different fetal monitoring technologies influence the work of midwives. Methods: Wireless and beltless 'non-invasive fetal electrocardiogram' (NIFECG) was trialled on 110 labouring women in an Australian maternity hospital. A focus group pertaining to midwives' experiences of using CTG was conducted prior to the trial. After the trial, midwives were asked about their experiences of using NIFECG. All data were analysed using thematic analysis. Findings: Midwives felt that wired CTG creates barriers to physiological processes. Whilst wireless CTG enables greater freedom of movement for women, it requires constant 'fiddling' from midwives, drawing their attention away from the woman. Midwives felt the NIFECG better enabled them to be 'with woman'. Discussion: Midwives play a pivotal role in mediating the influence of CEFM on women's experiences in labour. Exploring the way in which different forms of CEFM impact on midwives' practice may assist us to better understand how to prioritise the woman in order to facilitate safe and satisfying birth experiences. Conclusion: The presence of CEFM technology in the birth space impacts midwives' ways of working and their capacity to be woman-centred. Current CTG technology may impede midwives' capacity to be 'with woman'. Compared to the CTG, the NIFECG has the potential to enable midwives to provide more woman-centred care for those experiencing complex pregnancies.